Akademisk kunnskap og pedagogisk faglighet i barnehagen - Pettersvold, Mari (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
An increasing number of preschool teachers have a master's degree, and in Norway, employing preschool teachers with a master's-level education is a stated political objective. In both Norway and Denmark, there is growing demand for greater expertise in preschool and more career options for preschool teachers and educators. Thus, there is also a need for greater understanding about the impact of academic knowledge on preschool pedagogical practice. In this anthology, new empirical knowledge is presented on how master's-level competence is applied practically within the preschool context, and how academic knowledge is found relevant in practice. The empirical material that forms the basis of this anthology is qualitative interviews with master's-educated teachers in Norwegian and Danish preschools as well as a survey sent to all preschools in Norway. The anthology is also based on historical material and documents that highlight the rise of specialized education in general and master's education in particular. The book stems from the research project "Preschool master in practice", a collaborative project between researchers at one Danish and two Norwegian educational institutions: VIA University College in Århus, Oslo Metropolitan University, and the University of South-Eastern Norway. The aim of the project has been to increase understanding of how master's-educated preschool teachers' feel their particular expertise is put to use, and how their expertise benefits the preschool and creates opportunities within the sector.